1998
DOI: 10.1093/sleep/21.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Sleep Deprivation, Time of Day, and Driving Experience on a Driving Task

Abstract: Performance decrements after more than 24 hours of sleep deprivation (SD) are not only a monotonic function of the duration of SD, but are the result of an interaction between SD and time of day. The major deteriorations in performance during SD are still evident throughout the night, as in the non-sleep-deprived state. Twelve experienced and 12 inexperienced drivers drove a driving simulator for 20 minutes at 0800, 1100, 1400, 1700, and 2000 hours on two testing days. One testing day was conducted after a nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
2
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 0 publications
6
53
2
1
Order By: Relevance
“…Specifically, variability in lateral lane position significantly increased when drivers had lowered alertness levels, consistent with previous studies using the AusEd driving simulator (Howard et al, 2007;Vakulin et al, 2007), on other driving simulator tasks (George, 2000;George, Boudreau, & Smiley, 1996;Lenne, Triggs, & Redman, 1998), and during on-road driving (Philip, et al, 2005;Ramaekers & O'Hanlon, 1994). Previous studies have also noted significant variations outside the prescribed speed range with sleep loss (Arnedt, Wilde, Munt, & MacLean, 2001;Lenne, Triggs, & Redman, 1998), consistent with the current study. Whilst driving simulator performance does not provide an absolute measure of crash risk, it is related to on road driving performance (Philip et al, 2005) and these behaviors are indicative of unsafe driving (Brookhuis, De Waard, & Fairclough, 2003).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Specifically, variability in lateral lane position significantly increased when drivers had lowered alertness levels, consistent with previous studies using the AusEd driving simulator (Howard et al, 2007;Vakulin et al, 2007), on other driving simulator tasks (George, 2000;George, Boudreau, & Smiley, 1996;Lenne, Triggs, & Redman, 1998), and during on-road driving (Philip, et al, 2005;Ramaekers & O'Hanlon, 1994). Previous studies have also noted significant variations outside the prescribed speed range with sleep loss (Arnedt, Wilde, Munt, & MacLean, 2001;Lenne, Triggs, & Redman, 1998), consistent with the current study. Whilst driving simulator performance does not provide an absolute measure of crash risk, it is related to on road driving performance (Philip et al, 2005) and these behaviors are indicative of unsafe driving (Brookhuis, De Waard, & Fairclough, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…Exclusion criteria were: medical contraindications for the sleep deprivation protocol; a sleep disorder or sleep apnea (assessed by the Multiple Apnea Prediction Score questionnaire (score >0.5) (Maislin et al, 1995) and the Epworth Sleepiness Scale (ESS) (score >10) (Johns, 1993)); pregnancy; participants who could not tolerate having no cigarettes in a 12-hour period; high-level caffeine users, defined as five or more caffeinated beverages per day (Lenne, Triggs, & Redman, 1998); and visual impairment not correctable with glasses. There was a large range of hours spent driving for work per week in the group, ranging from 8 to 80 hours per week, with an average of 42.4 hours.…”
Section: Participantsmentioning
confidence: 99%
“…SDLP is a frequently used metric (George, 2004;Risser et al, 2000;Summala et al, 1996) that indexes road tracking error or "weaving". This increases as a driver loses control over the vehicle's lateral position (de Waard & Brookhuis, 1991;Lenne et al, 1998;Ramaekers, 2003). The standard deviation of steering wheel angle (SDSWA) was also measured.…”
Section: Experimental Designmentioning
confidence: 99%
“…A recent study examined performance on a simulated driving task at 0800, 1100,1400,1700, and 2000 after one night of sleep deprivation (Lenne, Triggs, & Redman, 1998). Comparing sleep-deprived participants to participants who had slept the night before, that study found increases in the standard deviations for maintenance of a lateral position and speed as well as in the average values of lateral position and speed.…”
Section: Discussion Performance Stability and Sleep Deprivationmentioning
confidence: 99%